A comparative analysis between intralesional 5-fluorouracil versus surgical excision with intralesional triamcinalone acetonide in keloid excision - Patel, Vasim Ismail; Thomas, Ritty Ann (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Keloids are characterized by an uncontrolled proliferation of fibrous tissue after injury of the skin and has been treated by various modalities. Recently, newer therapeutic modalities have been studied including intralesional 5-FU, verapamil, laser therapy, cryotherapy, silicone sheet dressings, irradiation, retinoids, tacrolimus, imiquimod and combination therapy. The aim of this study is to analyse the response of intralesional 5-FU alone with that of intralesional triamcinolone acetonide with surgical excision thus to provide the best possible treatment modality to patients. Methods: Sixteen patients having keloid in head and neck region were taken into the study and divided into two groups after a routine blood check-up. Group A intralesional 5-FU once in three weeks for six sessions. Group B surgical excision followed by intralesional triamcinalone acetonide once weekly for six sessions. Patients were followed up for one year. Results: In group A, 7 patients came for review regularly. Aesthetic improvement was excellent for 6 but was considerably painful for all. In group B, 8 patients came for regular review, 6 had minimal scarring and all patients complained of mild pain post operatively. Conclusions: Intralesional 5-FU can be a very effective treatment modality for keloids, with no recurrence noted, except for its poor tolerability owing to side effects such as pain, nausea and vomiting. Classical method of surgical excision followed by intralesional steroids is better tolerated but has higher recurrence rates.